2012
DOI: 10.1016/j.coviro.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

SARS coronavirus pathogenesis: host innate immune responses and viral antagonism of interferon

Abstract: SARS-CoV is a pathogenic coronavirus that emerged from a zoonotic reservoir, leading to global dissemination of the virus. The association SARS-CoV with aberrant cytokine, chemokine, and Interferon Stimulated Gene (ISG) responses in patients provided evidence that SARS-CoV pathogenesis is at least partially controlled by innate immune signaling. Utilizing models for SARS-CoV infection, key components of innate immune signaling pathways have been identified as protective factors against SARS-CoV disease, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
448
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(464 citation statements)
references
References 98 publications
(105 reference statements)
6
448
0
10
Order By: Relevance
“…Furthermore, it has been reported that proinflammatory cytokine mRNAs induced by LPS are more stabilized than in the absence of LPS (Dai et al, 2003;Kishore et al, 1999). Hypersensitivity of PRRs in response to their cognate ligands and enhanced expression of proinflammatory cytokines are contributing factors to severe clinical disease and a prolonged period of recovery (Cheng et al, 2012;Totura and Baric, 2012;Villinger et al, 1999;Wahl-Jensen et al, 2011). Thus, in cases of BRDC that involve BVDV-bacterial co-infections, enhanced pro-inflammatory cytokine secretion in response to bacterial LPS could contribute to more severe clinical disease.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, it has been reported that proinflammatory cytokine mRNAs induced by LPS are more stabilized than in the absence of LPS (Dai et al, 2003;Kishore et al, 1999). Hypersensitivity of PRRs in response to their cognate ligands and enhanced expression of proinflammatory cytokines are contributing factors to severe clinical disease and a prolonged period of recovery (Cheng et al, 2012;Totura and Baric, 2012;Villinger et al, 1999;Wahl-Jensen et al, 2011). Thus, in cases of BRDC that involve BVDV-bacterial co-infections, enhanced pro-inflammatory cytokine secretion in response to bacterial LPS could contribute to more severe clinical disease.…”
Section: Discussionmentioning
confidence: 94%
“…Downstream of ORF1, the genome also encodes for four structural proteins, the S (spike), E (envelope), M (matrix), and N (nucleoprotein) protein. These genes are interspersed with several additional luxury ORFs, which differ significantly among coronavirus in number, nucleotide sequence, gene order, and function; for SARS-CoV, most of these additional ORFs are indispensable for viral replication but many have been shown to antagonize the innate immune response and influence disease severity (Figure 1) [12]. …”
Section: Coronavirusesmentioning
confidence: 99%
“…Despite their large genome size, infectious particles of many coronaviruses can be recovered successfully in vitro using various technological platforms (AlmazĂĄn et al, 2014;Totura & Baric, 2012). One of the most effective strategies is either by direct introduction of a full-length cDNA infectious clone into permissible cells or by in vitro transcription of the clone followed by transfection of the full-length RNA.…”
Section: Introductionmentioning
confidence: 99%